Humility in Management - Argandoña, Antonio (Journal of business ethics, 2015)
Although virtues have gained a firm presence in the theory and practice of corporate management, humility is not ranked as one the chief virtues in the business world. In spite of this, it is an important virtue, contributing to the manager’s moral and professional quality and the development of the company’s human team. This paper explains the basic traits of humility in general and how they manifest in the manager’s life and profession, and shows, within the ethics of virtues, that it is not just a personal desideratum but a fundamental quality of a good manager and good management.